Green Insights Into Launaea Pinnatifida: Extraction Techniques, Phytochemicals, Anti-Oxidant And Anti-Microbial Evaluation - Annapurna Ojha; Rajendra Pal Singh Rathore (Revista Electronica de Veterinaria, 2024)
Aim: This study aimed to evaluate the extraction techniques, phytochemical composition, antioxidant potential, and antimicrobial properties of Launaea pinnatifida to explore its potential as a natural bioactive source. Methods: The plant leaves were extracted using hydro alcoholic and petroleum ether solvents. Phytochemical screening identified the presence of alkaloids, flavonoids, tannins, and other secondary metabolites. Quantitative estimation of total phenolic content (TPC) and total flavonoid content (TFC) was performed using spectrophotometric methods. Antioxidant activity was assessed using DPPH radical scavenging and reducing power assays, while antimicrobial activity was evaluated against E. coli, S. aureus, and C. albicans using the well diffusion method. Results: The hydro alcoholic extract demonstrated a higher yield (5.30%) compared to petroleum ether (0.82%). The TPC and TFC were recorded as 41.90 mg GAE/g and 35.83 mg QE/g, respectively. The DPPH assay showed an IC50 value of 52.41 µg/mL, indicating moderate antioxidant potential. The hydro alcoholic extract exhibited significant antibacterial activity against E. coli and S. aureus, particularly in the nanosponge and nanosponge gel formulations, while no antifungal activity was observed against C. albicans. Conclusion: The findings suggest that Launaea pinnatifida possesses promising antioxidant and antibacterial properties, supporting its potential use in pharmaceutical applications.